2010
DOI: 10.1186/1747-5341-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Assistive Technologies (AAT): socio-technology as a powerful tool for facing the inevitable sociodemographic challenges?

Abstract: Due to the socio-demographic change in most developed western countries, elderly populations have been continuously increasing. Therefore, preventive and assistive systems that allow elderly people to independently live in their own homes as long as possible will become an economical if not ethical necessity. These respective technologies are being developed under the term "Ambient Assistive Technologies" (AAT). The EU-funded AAT-project Ambient Lighting Assistance for an Ageing Population (ALADIN) has establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…In this research Global Positioning System (GPS) technology was used to follow the movements of senior citizens with dementia, whilst considering ethical aspects. (Schu¨lke et al, 2010) found that there is a conflict between perspective of elderlies, caretakers and family members about safety, privacy, and security factors. In this study, family members and caregivers of elderly were found to be far more concerned about safety and security compared to privacy and independency.…”
Section: Security and Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…In this research Global Positioning System (GPS) technology was used to follow the movements of senior citizens with dementia, whilst considering ethical aspects. (Schu¨lke et al, 2010) found that there is a conflict between perspective of elderlies, caretakers and family members about safety, privacy, and security factors. In this study, family members and caregivers of elderly were found to be far more concerned about safety and security compared to privacy and independency.…”
Section: Security and Safetymentioning
confidence: 99%
“…Moreover, this imposes substantial treat to the robot user's privacy since the personal data can be accessed and controlled by other parties. This may also encounter data abuse of the user's personal information (Schu¨lke et al, 2010;Friedwald et al, 2005).…”
Section: Privacymentioning
confidence: 99%
See 1 more Smart Citation
“…Permanently networked technologies has brought with it new surveillance issues for ethical architectural design according to Albrechtslund (2007). A number of authors have accordingly raised the spectre of a "big brother" society where it will be increasingly difficult to be left alone (Schülke et al, 2010;Wright et al, 2010) and the feeling of being under surveillance Langheinrich et al (2004). Similar concerns are raised about safety and security of intelligent environments (Aarts, 2004;Nixon et al, 2004;Van Hoof et al, 2007;Rashidi, 2012), and a trade-off between security/safety and privacy is recognised (Landau et al, 2010;Sharkey and Sharkey, 2012).…”
Section: Survey Of Ethical Issuesmentioning
confidence: 99%
“…This allows decisions to be made on the collected data . Van Heerde et al (2006) for example, note that it is the both high quality and large quantities of data that can be collected that enable the intelligence of AmI systems, whilst providing privacy challenges, which has the potential for misuse/abuse of this sensitive information (Friedewald, 2005;Schülke et al, 2010). Wright et al (2010) argue that ambient intelligence technology violates most existing privacy-protecting borders.…”
Section: Survey Of Ethical Issuesmentioning
confidence: 99%